2014
DOI: 10.1002/14651858.cd002745.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine and rimantadine for influenza A in children and the elderly

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 212 publications
1
19
0
Order By: Relevance
“…After the discovery of amantadine, rimantadine and a number of amantadine derivatives were later synthesized (300, 301), but they did not reach the market, except for amantadine and rimantadine. Despite their approval for adult patients, amantadine and rimantadine do not contribute to the prevention, treatment, or reduced duration of influenza A virus infection in children and the elderly (302). Because of widespread resistance, amantadine has virtually been abandoned in the treatment of influenza infections (303).…”
Section: Amantadine and Rimantadinementioning
confidence: 99%
“…After the discovery of amantadine, rimantadine and a number of amantadine derivatives were later synthesized (300, 301), but they did not reach the market, except for amantadine and rimantadine. Despite their approval for adult patients, amantadine and rimantadine do not contribute to the prevention, treatment, or reduced duration of influenza A virus infection in children and the elderly (302). Because of widespread resistance, amantadine has virtually been abandoned in the treatment of influenza infections (303).…”
Section: Amantadine and Rimantadinementioning
confidence: 99%
“…Surgical masks as physical barriers were also found to be an effective preventative intervention ( 3 ). Antiviral drugs such as Tamiflu can have a prophylactic effect ( 4 , 5 ), although possible side effects and the obligation to not medicate unnecessarily make this intervention something that should only be considered by those at high risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Alicyclic amines/aminoadamantanes amantadine and rimantadine, first described in 1985 as M2 protein blockers ( [60]; H + channel/viroporin; only type A viruses), are not recommended anymore for clinical use (WHO/US), due to rapid induction of viral resistance mutations: 100% of clinical isolates are resistant. A 2014 Cochrane review found no evidence for efficacy or safety of amantadine for the treatment of influenza A [6]. However, their structures may still be useful as scaffolds for the design of future M2 inhibiting drugs.…”
Section: Orthomyxoviridaementioning
confidence: 99%